The Effectiveness of The Selective Method in Developing Students' Reading Skill - Fathor Rosyid; Azisi (STAI Nurul Huda Kapongan Situbondo, 2022)
That what is used in this foreign language development institution focuses only on the method of translation. They need a way in which they can practice more in Arabic pronunciation. the researcher offers a solution for applying the selective method. Which makes the selective method here, make more middle school students read Arabic. So that it is able to achieve effective learning in the process of teaching and learning the Arabic language and succeed in achieving the desired goals. This research is quantitative research with an experimental design style. The type of research this research is pre-experimental design research. There were 18 students. The research data was obtained by performing pre- and post-testing. The results of the t-test were obtained at a significant level of 0.05 calculated value of 0.107. Thus, it can be concluded that the use of selective methods in increasing the pumpkin skill of seventh grade students.